PARAMETERS DEPENDENCE OF DRIVERS ON THEIR INFORMATION LOAD - , В. К., І. А., І. П. (Municipal economy of cities (Technical science), 2013)
The effect of information load on the parameters of the main drivers through quantitative analysis of EEG parameters that characterize the excitatory and inhibitory processes in the cerebral cortex.